The Effectiveness of Ura Mawashi Geri and Mae Geri Kicks in Earning Points at Brawijaya University Karate Championship 2024 - Revinda, Dea; Darmawan, Agus (Indonesian Journal of Sport Management, 2025)
This study aims to analyze the contribution of the Ura Mawashi Geri and Mae Geri kicking techniques to point acquisition in the final kumite round of the student category at the Brawijaya University Karate Championship 2024. The main focus of this study is to determine which kicking technique is more effective in point acquisition, a key issue that the author addresses in this research. The sampling technique used is purposive sampling, where each athlete who reaches the final kumite round in the student category at the Brawijaya University Karate Championship 2024 is included as a sample. The method used in this research is direct observation, with supporting tools such as score sheets and a mobile phone camera. The data processing and analysis are conducted using percentage formulas. The study found that at the Brawijaya University Karate Championship 2024, the effectiveness of the Ura Mawashi Geri kicking technique in the final kumite round of the student category was 74%, with a failure rate of 26%, while the success rate of the Mae Geri kicking technique in the same round was 30%, with a failure rate of 70%. Based on these findings, it can be concluded that the more effective kicking technique for point acquisition in the student kumite category at the Brawijaya University Karate Championship 2024 is the Ura Mawashi Geri, with a success rate of 74%.